METHOD DEVELOPMENT AND VALIDATION OF LOPINAVIR IN TABLET DOSAGE FORM USING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY - Namratha, Sunkara; A, Vijayalakshmi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Reversed-phase high-performance liquid chromatographic method (RP-HPLC) was developed for the assessment of lopinavir in the dosage form of tablet. Methods: Chromatogram was run through using Kromosil C18 4.5Ã—150 mm using a mobile phase methanol: water of ratio 65:35% v/v with a rate of flow of 0.8 ml/min, measured by UV spectrometric detection at 265 nm. The method developed was validated in terms of precision, accuracy, linearity, and robustness parameters. Results: Retention time of lopinavir established at 2.482 min and percentage R.S.D of lopinavir found to be 1.0% and 0.5%, respectively. The method shows that good linearity range of 30â€“150 Î¼g correlation coefficient of lopinavir was 0.997. The limit of detection was 2.97 and limit of quantification was 9.92, respectively. The percent purity of lopinavir was 99.87%. Conclusion: The suggested method (Rp-HPLC) for concurrent assay lopinavir was validated, which is appropriate method for the analysis of lopinavir quantitatively in tablet dosage forms and bulk.